Soft-Switched Quasi-Single-Stage Dual-Active-Bridge Converter with Unsymmetrical H-Bridge Triangular Modulation - Jena P.; Barnawal P.J.; Singh R.K.; Lal V.N. (My University, 2025)
In this paper, a novel soft-switching-technique for quasi-single-stage (QS2) bidirectional DC-AC dual-active-bridge (DAB) converter is presented. The soft-switching-technique results in the triangular transformer current due to unsymmetrical switching of DC side H-bridge. DC side H-bridge of QS2 DAB consists of two branches, one branch supplied with fixed ON time pulse width modulation (PWM) signal. However, a variable ON-time controlled PWM is provided to another branch of the H-bridge. Due to this nature of switching, unsymmetrical H-bridge triangular modulation (TRM) is referred. The proposed modulation offered several advantages such as 1) near unit power factor correction (PFC) operation for bidirectional flow. 2) zero current switch (ZCS) turn ON and OFF for pulsating DC side H-bridge. 3) zero voltage switch (ZVS) turn ON and ZCS turn OFF for the switches of branch 2. 4) ZVS/ZCS turn ON for the switches of branch 1. 5) true soft-switching over the whole envelop of the line frequency. 6) improved performance with reduced total harmonics distortion (THD). A scale-down experimental prototype of 580 W is developed and the proposed technique is realized using TMS320F28335. A good power factor of 99.98% and THD of less than < 2.71% with peak experimental efficiency of 95.7% achieved using the proposed modulation technique. © 2023 IEEE.